Epistemology of Legal Interpretation: History, Limitations, and Deviations - Mumtazah, Nadia; Amini, Nur Fajriyah; Yelfadillah, Yelfadillah (Mashadiruna Jurnal Ilmu Al-Qurân dan Tafsir, 2026)
This study examines hukmi interpretation as one approach to interpreting the Qur'an, focusing on its treatment of verses on Islamic law. Through a descriptive-analytical approach based on literature studies, this research traces the history of the emergence, epistemological characteristics, and methodological dynamics of hukmi interpretation from the time of the Prophet to the period of classical interpretation codification and its development in the modern era. The findings show that hukmi interpretation emerged in the context of sectarian debates and taqlid practices that influenced the methodological consistency of interpretation, with frequent mixing of the bayani and istinbati approaches. Socio-political factors and sectarian fanaticism also contributed to methodological deviations that influenced the understanding of law in hukmi interpretation. This research contributes to the understanding of the construction of legal knowledge in the tradition of interpretation, highlighting the importance of contextual and epistemological approaches for the development of a more objective and critical contemporary Islamic legal interpretation.